2020
DOI: 10.1109/access.2020.3009125
|View full text |Cite
|
Sign up to set email alerts
|

cACP-2LFS: Classification of Anticancer Peptides Using Sequential Discriminative Model of KSAAP and Two-Level Feature Selection Approach

Abstract: Cancer is a leading killer disease globally, it occurs when the cellular changes cause the abnormal growth and division of the cells. Conventional treatment such as therapies and wet experimental methods are deemed unsatisfactory and worthless because of its huge cost and laborious nature. However, the recent innovation of anticancer peptides (ACPs) offers an effective way to treat cancer affected cells. Due to the rapid growth of biological sequences, truly identification of ACPs has become a difficult task f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…GAN has many real applications in different fields of life. For instance, improving cybersecurity [ 69 ], predictors in healthcare [ 70 ], stock market prediction [ 71 ], producing animation models[ 72 ], editing photographs, and image translation are popular applications [ 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…GAN has many real applications in different fields of life. For instance, improving cybersecurity [ 69 ], predictors in healthcare [ 70 ], stock market prediction [ 71 ], producing animation models[ 72 ], editing photographs, and image translation are popular applications [ 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that the natural biological properties of peptides are a complex combination of hydrophobicity, charge, molecular mass, reduction of the hydrophobic moment [1], and other physicochemical characteristics which can provide useful information in classifying, predicting, and synthesizing new peptides [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to propose a computationally effective model, we used the eXtreme Gradient Boosting-Recursive Feature Elimination (XGB-RFE) to choose the optimal features from the heterogeneous feature vector. Moreover, the predictive rates of the extracted spaces are investigated via several learning models namely, Extra trees classifier (ETC) [34], XGBoost (XGB) [35], Support vector machine (SVM) [36,37], AdaBoost (Ada) [38], Fuzzy KNN (FKNN) [39], and Light Gradient Boosted Machine (LGBM) [40]. The flow diagram of our proposed model is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%